(untitled) (Palimpsesto, 2023)
The present writing proposes, in ten theses built through the Nietzschean method of dramatization, that all use, consumption or activity, can be conceived as a machine that is mounted on a line of flight of an individual or a group, subjectifying, singling out and increasing the power. But addiction can also set up a capture device capable of subtracting power, dominating one’s life, and destroying the entire existential territory, at the same time that it serves -paradoxically- to stabilize current societies. It is concluded that an addiction machine is productive when it is regulated by means of a plan based on an ethic of prudence; that is, when it is in favor of life.